Visual Cryptographic Mechanism for Secret Information Sharing - Kumar H.R, Prasanna; Niranjan N. Chiplunkar, Dr (International Journal of Engineering and Technology, 2018)
Security and confidentiality aspects are very much essential for sharing secret information. To provide security to the information conventional encryption technique may be used; which requires high computation and the security is also not in acceptable level. The quality of input image and the recovered image is same. The other approach involves use of visual cryptographic techniques where shares are created for the secret images and the recovered image quality is an issue. We proposed a method for transferring confidential image, which make use of two stages during encryption. Instead of sending the confidential image directly to the receiver, send an encrypted form of the image along with three shares. During decryption decrypt the encrypted image using random numbers and flag values. The proposed method provides multi- layered security for transmitting the confidential image.Â Â